Utility of Pacemaker With Sleep Apnea Monitor to Predict Left Ventricular Overload and Acute Decompensated Heart Failure - Augusto, J (2019)
Pacemakers with sleep apnea monitor (SAM) provide an easy tool to assess obstructive sleep apnea over long periods of time. The link between respiratory disturbances at night and the incidence of acute decompensated heart failure (ADHF) is not well established. We aimed at (1) determining the ability of SAM pacemakers to evaluate the extent of left ventricular overload and (2) assess the impact of respiratory disturbances at night on the occurrence of ADHF over 1-year of follow-up. We conducted a single-center prospective study. Consecutive patients with SAM pacemakers were comprehensively assessed. SAM automatically computes a respiratory disturbance index (RDI, apneas/hypopneas per hour - AH/h) in the previous night and the percentage of nights with RDI >20 AH/h in the previous 6 months. Thirty-seven patients were included (79.3 ± 11.2 years, 46% males). A high RDI in the previous night and a higher %nights with increased RDI were associated with increased NT-proBNP values (p = 0.008 and p = 0.013, respectively) and were the sole predictors of increased noninvasive pulmonary capillary wedge pressures (PCWP) in the morning of assessment (p = 0.031 and p = 0.044, respectively). Receiver operating characteristic curve analysis revealed an area under the curve of 0.804 (95% confidence interval 0.656 to 0.953, p = 0.002) for %nights with RDI >20 AH/h in the prediction of high PCWP. Patients with >12.5% of nights with RDI >20AH/h tended to have more ADHF during follow-up (log-rank p = 0.067). In conclusion, a high burden of apneas/hypopneas at night is associated with elevated NT-proBNP and PCWP values and an increased risk of ADHF over 1 year. These patients might benefit from early tailored clinical management.